Edukasi mitigasi bencana banjir pada masyarakat di Kelurahan Tanjung Selamat, Sumatera Utara - Pujiati, Pujiati; Siregar, Ameilia Zuliyanti; Iskandarini, Iskandarini (Piramida Akademi, 2025)
The flood disaster mitigation education program aims to enhance the community's understanding and preparedness in facing disaster risks, particularly floods, which frequently occur in Tanjung Selamat Sub-district, North Sumatra. This initiative is driven by the high vulnerability of the area to flooding and the importance of equipping the public with knowledge on self-rescue procedures before, during, and after a disaster. The method employed in this community service program was descriptive, involving public outreach, hands-on mitigation training, interactive discussions, and program evaluation. Activities included expert-led sessions, evacuation simulations using role-playing techniques, and the use of audiovisual media to reinforce participants' understanding. The results indicated improved knowledge, skills, and awareness among participants regarding flood mitigation. Community members from various age groups and social backgrounds actively participated and showed enthusiasm throughout the program. Additionally, flood mitigation tools such as life jackets and informational materials were distributed to support preparedness efforts. This initiative demonstrates that structured and participatory education can build responsive, resilient, and compassionate communities in the face of disaster. The flood disaster mitigation education is expected to serve as a model for empowering communities in disaster-prone areas.